Azithromycin-Associated Choreoathetosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at Women and Children's Hospital of Buffalo, NY, report an 11- year-old boy with a history of developmental delay who developed transient agitation and choreoathetoid movements of upper extremities in temporal relation to treatment of influenza A and B respiratory infections with oral azithromycin on 2 occasions.